Differences in maternal behavior and development of their pups depend on the time of methamphetamine exposure during gestation period - Malinová-Ševčíková, M; Hrebíčková, I; Macúchová, E; Nová, E; Pometlová, M; Šlamberová, R (Physiological research, 2014)
The present study examined the hypothesis that the extension of noxious effect of methamphetamine (MA) on maternal behavior and postnatal development on the pups may differ in dependence with time of application. Female rats were injected with MA (5 mg/kg) or saline during first (embryonic day (ED) 1-11) or second (ED 12-22) half of gestation. Our results demonstrated that MA exposure on ED 12-22 led to decreased birth weight and weight gained during lactation period relative to rats treated on ED 1-11. Both sexes treated prenatally with MA on ED 1-11 opened eyes earlier compared to animals treated on ED 12-22. As a matter of sensorimotor development application of MA on ED 1-11 impaired the righting reflex, while MA exposure on ED 12-22 impaired the performance of beam balance test in male rats. There were no differences in maternal behavior. Therefore, it seems that MA exposure in the first half of the gestation impaired the early sensorimotor development that is under control of the brain stem, while the MA exposure in the second half of gestation affected the beam balance performance that is dependent on the function of the cerebellum.
Keywords: Random Allocation; Animals, Newborn; těhotenství; Rotarod Performance Test; Rats, Wistar; mužské pohlaví; novorozená zvířata; Central Nervous System Stimulants; růst a vývoj; ženské pohlaví; zvířata; Maternal Behavior; methamfetamin; mateřské chování; metoda rotující tyčky; Pregnancy; zpožděný efekt prenatální expozice; náhodné rozdělení; stimulanty centrálního nervového systému; potkani Wistar; Methamphetamine; Female; Growth and Development; Prenatal Exposure Delayed Effects; Male; Animals